Assessing the atomic structure of the defect complex in a solid electrolyte by photoluminescence measurements. (10th February 2021) - Tanimoto, Naoki; Nagai, Masaya; Ashida, Masaaki; Okuyama, Yuji; Kani, Yukimune
Abstract: We demonstrate that photoluminescence in solid electrolytes is sensitive to the atomic structure of the defect complex that is decisive to the ionic conduction. We systematically measure the photoluminescence spectra of a typical solid oxide electrolyte, stabilized zirconia sintered pellets. Based on the comparison with the photoluminescence spectrum of a single crystal, we assign the broad long-lived photoluminescence band in the visible region near 2.4 eV to that related to the defect complex. Because the electronic state of the oxygen vacancy is sensitive to the surrounding ions, which has been indicated in previous investigations of the local structure around the dopants and vacancies, we are able to assign each sample's photoluminescence characteristics to a certain atomic arrangement that is considered plausible based on previous investigations. Photoluminescence spectroscopy is applicable to various solid electrolytes and can become a powerful tool for their characterization.